2019
DOI: 10.4102/sajce.v9i1.672
|View full text |Cite
|
Sign up to set email alerts
|

Accountability of school stakeholders in ensuring orphaned children’s school attendance

Abstract: Research has established that orphans are more often absent from school than non-orphans (Operario et al. 2008). Campbell et al. (2016) believe that when orphaned children do not attend school, they miss out on food parcels and clothing material donated by the Non-governmental organizations (NGOs) to the learners at school. The learners also miss opportunities to socialise with other children and the support from welfare organisations. According to the South African Schools Act, learners from Grade 1 to Grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Most orphaned children fall behind in school because they have had to care for an ailing parent or family members, particularly those suffering from HIV/AIDSrelated illnesses (Breckenridge et al, 2019:513). Similar findings have been reported in other studies (Bennell, 2021;Ntuli et al, 2020;Ogina and Ramare, 2019). It was found that OVC face challenges when attempting to access basic education, such as a lack of material resources and emotional support.…”
Section: (B) Impact On Educationsupporting
confidence: 89%
“…Most orphaned children fall behind in school because they have had to care for an ailing parent or family members, particularly those suffering from HIV/AIDSrelated illnesses (Breckenridge et al, 2019:513). Similar findings have been reported in other studies (Bennell, 2021;Ntuli et al, 2020;Ogina and Ramare, 2019). It was found that OVC face challenges when attempting to access basic education, such as a lack of material resources and emotional support.…”
Section: (B) Impact On Educationsupporting
confidence: 89%
“…Empathy has been considered the distinguishing feature motivating caring practice amongst educators (Zembylas 2008 ). Many sub-Saharan African studies have similarly highlighted pastoral acts of care by teachers towards children in need at school (Ogina 2010 ; Ogina & Ramare 2019 ); and whilst these caring behaviours are well intended and appreciated, they are often too individual and personalised to promote any long-term care for CLHIV that is sustainable (Campbell et al 2016 ; Skovdal & Evans 2017 ). Research points to the need for a more deliberate, systematic, institutionalised ethic of care to be practised at schools to encourage a sustained supportive school environment for CLHIV (Campbell et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the African traditional culture, there were no orphans as parentless children were cared for within kin systems, but due to poverty and other strains, families increasingly became less willing or unable to take care of orphans while others started taking advantage of them (Pollack & Fishman, 2020). In addition, African researchers indicate that HIV and AIDS besides wars worsened the devastation of African families, hence creating the necessity for orphanages in addition to national and international adoptions in the 20th century (Ogina & Ramare, 2019).…”
Section: Introductionmentioning
confidence: 99%